2022
DOI: 10.13189/saj.2022.100423
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Plyometric Circuit Training before and after Technical Training on Cardiorespiratory and Power Abilities of Junior Male Volleyball Athletes

Abstract: This study aimed to determine the effect of plyometric circuit training on cardiorespiratory and power abilities in male volleyball athletes. This study was experimental research with a Quasi-Experimental Design that involved male volleyball athletes from the Yuso Sleman Club as the population. The sample included 20 athletes determined by ordinal pairing, which were then divided into two groups. Using the multistage test, the first group was utilized to measure cardiorespiratory ability (VO 2 max). Meanwhile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The characteristic of plyometric training is resistance training that uses body weight as the weight that focuses on the utilization of fast muscle concentration contraction period after the muscle experience fast eccentric mode [18]. Many research findings have reported that plyometric training could improve muscle power, such as in junior volleyball athletes [19] and football athletes, especially in improving muscular power and leg strength [20]. The advantage of plyometric training for junior athletes is improving sports performance, being prepared to join the next training or competition, strengthening the bones, and being safe [21].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic of plyometric training is resistance training that uses body weight as the weight that focuses on the utilization of fast muscle concentration contraction period after the muscle experience fast eccentric mode [18]. Many research findings have reported that plyometric training could improve muscle power, such as in junior volleyball athletes [19] and football athletes, especially in improving muscular power and leg strength [20]. The advantage of plyometric training for junior athletes is improving sports performance, being prepared to join the next training or competition, strengthening the bones, and being safe [21].…”
Section: Discussionmentioning
confidence: 99%
“…Plyometric training is used in many sports, speaking specifically of volleyball, a high -speed discipline where plyometric training programs play an important role in enhancing the performance of athletes [24] and improving their jumping abilit y [25] in addition to their strength and cardio respiratory skills [26]. On the other hand, soccer is a team sport that requires great physical demand, including speed, agility and plyometric skills such as changes of direction and jumps [27] to achieve high performance.…”
Section: Introductionmentioning
confidence: 99%